ANALYSİS OF ELECTRİCAL CONDUCTİVİTY İN NANOTRANSİSTOR STRUCTURES WİTH GRAPHENE OXİDE NANOFİBERS - Khanmamadova , E. (Collection of scientific papers «ΛΌГOΣ», 2023)
In this article, an overview of the properties and application potential of graphene oxide-based nanofibers is presented. The electrical conductivity of graphene oxide nanofibers and nanotransistor structures is determined depending on the electrical properties of these materials and structures. Graphene oxide nanofibers are a material obtained by the oxidation process of graphene, and electrical conductivity is one of the main functions of batteries and transistors.